Import-based market experience and firms’ exit from export markets - Choquette, Eliane (Journal of International Business Studies, 2019)
Empirical evidence shows that firms’ internationalization process can be non-linear and often includes de-internationalization events. This study focuses on one type of de-internationalization event – a firm’s decision to exit an export market – and asks how international experience affects its probability of occurrence. In particular, this study complements existing literature by looking at the effect of import-based market experience – considered as a source of market-specific knowledge prior to export market entry – on the probability of a firm exiting an export market. Conceptually, this study contrasts two views on the consequences of increased market knowledge and hypothesizes that, from a learning perspective, import-based market experience ought to reduce export market exit, whereas, from a sunk cost logic, it ought to increase export market exit. Using duration analysis of detailed data on the internationalization history of 1920 Danish firms, I find that the sunk cost logic primarily explains the relationship between import-based market experience and a firm’s probability to exit an export market, and that the effect is strongest for exports to similar destinations. Further analysis shows that this result is partly driven by experimentation-like export behavior by firms with import-based market experience.